Soft Bioelectronics: A Chest‐Laminated Ultrathin and Stretchable E‐Tattoo for the Measurement of Electrocardiogram, Seismocardiogram, and Cardiac Time Intervals (Adv. Sci. 14/2019). Issue 14 (17th July 2019) - Ha, Taewoo; Tran, Jason; Liu, Siyi; Jang, Hongwoo; Jeong, Hyoyoung; Mitbander, Ruchika; Huh, Heeyong; Qiu, Yitao; Duong, Jason; Wang, Rebecca L.; Wang, Pulin; Tandon, Animesh; et al.
Abstract : In article number1900290, Nanshu Lu and co‐workers create a noninvasive, ultrathin, and stretchable e‐tattoo capable of electro‐mechano‐acoustic cardiovascular (EMAC) sensing to synchronously measure electrocardiogram (ECG) and seismocardiogram (SCG), which can be used to extract various cardiac time intervals and infer systolic and diastolic blood pressure beat‐to‐beat. A 3D digital image correlation (DIC) method is applied to map human chest displacement to determine the best location for e‐tattoo attachment.